Pathways to scale finance for digitalisation on the path to agricultural transformation - Visser, Piet; Ameringen, Marc van; Rwakigumba, Ronald (Technical Centre for Agricultural and Rural Cooperation, 2018)
Using digital farmer profiles in management and planning helps facilitate farmers with financial services like loans and savings